Uncertainty and fiscal policy in an asymmetric monetary union - Carsten Hefeker; Blandine Zimmer (Center for Economic Studies and ifo Institute (CESifo), 2008)
The paper examines the monetary-fiscal interactions in a monetary union model with uncertainty due to imperfect central bank transparency. We first show that monetary uncertainty disciplines fiscal policymakers and thereby reduces taxes, average inflation and output distortions. However, as more members enter the monetary union, the fiscal disciplining effect of uncertainty is mitigated. As a consequence, monetary union enlargement may lead to a more aggressive fiscal stance in some member countries, depending on their relative economic and political weights, on their government's spending target, and on the change in the degree of uncertainty that they experience with the enlargement.
Keywords: E58; E63; F36; 330; Geldpolitik; Unvollkommene Information; Risiko; Finanzpolitik; Entscheidung bei Unsicherheit; Währungsunion; Theorie